Daring to regulate coca and cocaine: Lessons from Colombia's drug war trenches (2022)
This essay is from a Beckley Foundation Report, commissioned and convened by Amanda Feilding for the Beckley Foundation¿s Global Initiative for Drug Policy Reform, called The Cocaine Papers. This Report is the latest in the Beckley Foundation's "Roadmaps to Regulation" series, and will be published later this year. It is a critical review of Colombia¿s 2020 legislative proposal (law project 236) to regulate the coca leaf and cocaine markets, authored by Senator Iván Marulanda and co-sponsored with Senator Feliciano Valencia. The essay provides a qualitative analysis of the regulatory regime proposed, its effects across the supply system, and the associated benefit and cost outcomes for Colombia. The essay concludes with a reflection on the challenges surrounding the adoption of coca leaf and cocaine regulation and offers lessons to overcome the political barriers to policy change